Zastosowanie miar maksymalnej straty na kapitale w badaniu efektywności funduszy hedgingowych - Pruchnicka-Grabias, Izabela (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper presents research on hedge funds efficiency with such measuresas Calmar ratio, Sterling ratio and Burke ratio carried out using the data fromHedge Fund Research database for 2005–2011. The aim of the study is to answerthe question whether alternative efficiency measurs are really more adequate for assessing the efficiency of hedge fund investments. So far, the answer to thisquestion is surprisingly negative.